Synthesis and characterization of pendant carboxylic acid functional poly(lactic acid) and poly(lactic acid-co-glycolic acid) and their drug release behaviors - KAYAMAN APOHAN, NİLHAN (WILEY, 2005)
The carboxylic acid functionalized biodegradable aliphatic polyesters were prepared by ring-opening polymerization of L-lactide and glycolide with 2,2'-bis(hydroxymethyl propionic acid) (HMPA) as an initiator. The polymers were characterized by FT-IR, H-1-NMR and gel permeation chromatography (GPC). Molecular weights of homopolymers and copolymers ranged from 0.28 X 10(4) to 11 X 10(4) and decreased with increasing weight fraction of HMPA in the feed. Moreover by changing the HMPA content, the solubility and degradation behavior of resulting polymers could be varied. Environmental scanning electron microscopy (ESEM) studies revealed that the microspheres were spherical in shape and had a smooth surface texture. For the investigation of drug release behavior of biopolymers, Lidocain was used as a model ionic drug. It was observed that an increase in drug loading reduces the encapsulation efficiency. After the initial burst, the release rate of the drug increased with time, with most of the drug released within 15 days. Copyright (c) 2005 John Wiley & Sons, Ltd.
Keywords: poly(lactic acid); poly(glycolic acid); degradation; drug delivery systems; ring-opening polymerization; MICROSPHERES; COPOLYMERIZATION; DEGRADATION; MICROPARTICLES; SOLVENT